STRATEGY FOR ENSURING FINANCIAL SECURITY OF TEXTILE ENTERPRISES - Tursunov Bobir Ortikmirzaevich (Scholar Express Journals, 2024)
In this paper has been suggested ways to eliminate economic and financial risks in enterprises, substantiates ways to eliminate economic and financial risks in enterprises, mechanisms for optimal management of ensuring financial security in enterprises, and proposes a strategy for ensuring financial security in enterprises.
Keywords: Financial Security; Multivariate Analysis; Dispersion